Antifouling Activity of Epibiotic Bacteria Associated with Soft Coral Sarcophyton sp. Collected from the Central Red Sea - S. Mutadaris, Shatha; Lafi Al Solami, Lafi (Journal of King Abdulaziz University: Marine Sciences, 2022)
The microbial communities associated with marine invertebrates are considered as a prolific source of bioactive metabolites. In this study, the bacteria associated with the soft coral Sarcophyton sp. collected from the Red Sea was screened for antifouling activity to identify potential natural antifouling compounds. The extract of bacterial strain Ruegeria lacuscaerulensis KAU-MB3 associated with the soft coral showed strong antifouling activity in laboratory assays. The crude bacterial extract reduced the growth of biofilm-forming bacteria and inhibited the biofilm formation significantly. Barnacle larval settlement assay indicated a significant reduction in the settlement of larvae treated with the crude extract. The crude extract was analysed by GC-MS to understand the chemical composition. GC-MS results revealed the presence of compounds such as hexadecane, octatriacontyl pentafluoropropionate, cis-Z-à-bisabolene epoxide and geranyl isovalerate. In conclusion, this study indicated that the bacteria associated with the soft corals could be used as one of the potential sources for the natural product antifoulants.